EFEKTIVITAS PEMANFAATAN MEDIA SOSIAL FACEBOOK DALAM MENINGKATKAN VOLUME PENJUALAN: Studi Pada UMKM Permen Tape “REZEKI” Ngadiluwih Kediri - Dwi Restanti, Yani (Universitas Pawyatan Daha, 2023)
REZEKI tape candy business actors want to expand their market share and target market by utilizing Facebook social media because Facebook provides many facilities for businesses by implementing Facebook Marketing. The purpose of this study is to find out how effective the use of Facebook social media is to increase sales volume of REZEKI tape candy, in Ngadiluwih District, Kediri Regency. The type of research used is qualitative research using a descriptive approach. data collection techniques through interviews with industry owners, direct observation of the tape candy industry, and documentation in the form of photos, video or audio and data analysis techniques include data collection, reduction and data categories, data display and drawing conclusions. The results of the study inform that Facebook social media is effective for increasing sales volume by utilizing the features on Facebook. There are many benefits to be gained from online business by utilizing Facebook social media. REZEKI tape candy business actors provide COD delivery and payment facilities. The results of interviews with Tape candy business owners informed that by utilizing Facebook it was proven that there was an increase in sales volume with the large number of markets served. It is hoped that in the future the tape candy business owner can expand the market share served.